Sulfonamide antibiotic reduction in aquatic environment by application of fenton oxidation process - Dehghani, Somayyeh (BioMed Central, 2013)
Presence of antibiotics in the environment may cause potential risk for aquatic environment and organisms. In this research, Fenton oxidation process was offered as an effective method for removal of antibiotic sulfamethoxazole from aqueous solutions. The experiments were performed on laboratory-scale study under complete mixing at 25±2°C. The effects of initial antibiotic concentration, molar ratio of H(2)O(2)/Fe(+2), solution pH, concentration of H(2)O(2), Fe(+2) and reaction time was studied on the oxidation of sulfamethoxazole in three level. The results indicated that the optimal parameters for Fenton process were as follows: molar ratio of [H(2)O(2)]/[Fe(+2)] = 1.5, pH= 4.5, and contact time= 15 min. In this situation, the antibiotic removal and COD reduction were achieved 99.99% and 64.7-70.67%, respectively. Although, Fenton reaction could effectively degrade antibiotic sulfamethoxazole under optimum experimental conditions, however, the rate of mineralization was not completed. This process can be considered to eliminate other refractory antibiotics with similar structure or to increase their biodegradability.